Producción y uso del hongo Trichoderma harzianum en el control de moniliasis (Moniliphthora roreri) en mazorcas de cacao - Torres Fajardo, Marjorie Mariana (2023)
Moniliasis is one of the most important fungal diseases in cocoa cultivation because it affects the pods with high severity, and is one of the limiting factors of productivity. The fungus Moniliophthora roreri is the causal pathogen of this disease. For the control of moniliasis there are several management strategies such as: cultural control, biological control and chemical control, the latter being the most widely used in the country despite the high risk to the environment. In the present research work, the objectives were: To describe the production and use of the fungus Trichoderma harzianum in the control of moniliasis (Moniliophthora roreri) in cocoa pods; to explain the production of this kind of fungus, and to specify its use as a natural controller of the precursor fungus of the moniliasis disease (M. roreri) in cocoa pods. Regarding the methodology and techniques used, these were of exploratory and explanatory type; exploratory because it was centered on already existing information and technical documents, from where all the information was compiled and then classified, tabulated, paraphrased and explained in relation to the proposed objectives; the methodology is also explanatory, because it details the relationship that exists between the causal agent of the Moniliasis disease of cocoa (Moniliophthora roreri) and its organic antagonistic agent Trichoderma harzianum. The conclusions indicate that the use of T. harzianum, an antagonistic organism of Moniliophthora roreri, contributes to the health, yield and safety of the cocoa crop, as well as reducing the unfavorable environmental impact caused by the frequent use of chemical products for pest control. The use of the fungus T. harzianum for the management of the moniliasis disease is an alternative to achieve increases in yields, quality and resilience of the crop; consequently, the production and use of T. harzianum in cocoa plantations in the country is recommended.